Differential analysis of immune reconstitution after allogeneic hematopoietic stem cell transplantation in children with Wiskott-Aldrich syndrome and chronic granulomatous disease - Zhou, Ya; Zhang, Luying; Meng, Yan; Lei, Xiaoying; Jia, Lanzhou; Guan, Xianmin; Yu, Jie; Dou, Ying (Frontiers in Immunology, 2023)
Objective To investigate similarities and differences in immune reconstitution after allogeneic hematopoietic stem cell transplantation (allo-HSCT) in children with Wiskott-Aldrich syndrome (WAS) and chronic granulomatous disease (CGD). Method We retrospectively analyzed the lymphocyte subpopulations and the serum level of various immune-related protein or peptide on Days 15, 30, 100, 180 and 360 post-transplantation in 70 children with WAS and 48 children with CGD who underwent allo-HSCT at the Transplantation Center of the Department of Hematology-Oncology, Children’s Hospital of Chongqing Medical University from January 2007 to December 2020, and we analyzed the differences in the immune reconstitution process between the two groups. Results ① The WAS group had higher lymphocyte subpopulation counts than the CGD group. ② Among children aged 1-3 years who underwent transplantation, the WAS group had higher lymphocyte subpopulation counts than the CGD group. ③ Further comparisons were performed between children with non-umbilical cord blood transplantation (non-UCBT) and children with umbilical cord blood transplantation (UCBT) in the WAS group. On Day 15 and 30 post-transplantation, the non-UCBT group had higher B-cell counts than the UCBT group. On the remaining time points post-transplantation, the UCBT group had higher lymphocyte subpopulation counts than the non-UCBT group. ④ Comparisons were performed between children with non-UCBT in the WAS group and in the CGD group, the lymphocyte subpopulation counts were higher in the WAS group compared to the CGD group. ⑤ On Day 100 post-transplantation, the CGD group had higher C3 levels than the WAS group. On Day 360 post-transplantation, the CGD group had higher IgA and C4 levels than the WAS group. Conclusion ① The rate of immunity recovery was faster in children within the WAS group compared to those children within the CGD group, which may be attributed to the difference of percentage undergoing UCBT and primary diseases. ② In the WAS group, the non-UCBT group had higher B-cell counts than the UCBT group at Day 15 and 30 post-transplantation, however, the UCBT group had higher B-cell counts than the non-UCBT group at Day 100 and 180 post-transplantation, suggesting that cord blood has strong B-cell reconstitution potentiality after transplantation.